"Oral" tribology study on saliva-tea compound mixtures: Correlation between sweet aftertaste (Huigan) perception and friction coefficient. (November 2019) - Chong, Pik Han; Chen, Jianshe; Yin, Danting; Upadhyay, Rituja; Mo, Linyi; Han, Lei
Abstract: Sweet aftertaste (Huigan) is a sensation perceived after drinking tea, and lasts in the mouth and throat, leading to salivation for an extended period of time. The study aimed to reveal the underpinning mechanisms of Huigan and the its influencing factors. Tribology approach was applied to this study in conjunction with sensory analysis and other physiology assessments. Tea compounds of commercial interest were selected for the study. Preliminary sensory tests of 24 subjects were carried out to evaluate the Huigan intensity of these tea compounds. Based on these tests, 12 subjects were selected and divided into two groups, each with 6 subjects: sensitive subjects and non-sensitive subjects. In vitro tribology measurements were made for samples prepared either prepared as 1:1 mixtures of tea compound solution and human whole saliva or expectorated tea compound solutions along with the saliva which were collected from the subjects after oral processing. The Huigan intensity perceived by the sensitive group was found to be highly correlated with the friction coefficient measured, especially at the sliding speeds lower than 0.5 mm/s. Graphical abstract: Unlabelled Image Highlights: Sensitivity of sweet aftertaste from tea compounds varies among individual. Human saliva affects the lubrication behavior of certain tea compounds. Sweet aftertaste is highly correlated with friction at low speed in sensitive group. Ex vivo methodology reveals a real saliva-food system in tribology study.